Evaluasi Kebijakan Pendidikan Di Sekolah Smp It Nurul Ilmi Medan - Al-Fatih, Muhammad; Tia Pratiwi; Sri Rahayu Ningsih (Institut Teknologi dan Bisnis (ITB) Semarang, 2024)
This research aims to findout that education policy evaluation is a procedure used to assess how much aneducational policy produces results using a comparison between goals and targets with the results obtained. the procedure must be carried out at the timeof implementing the implementation of the education policy analysis, which aimsto find out how the education policy is running, whether it is running well or is experiencing obstacles, changes are needed or only improvements. In addition, the evaluation of educational policies provides clarity about the advantages and disadvantages of the applied educational policies, we can also find out all the impacts that have been caused by the education policies, whether they cause benefits or even provide losses, chaos and so on. At the management stage, the evaluation process is the last stage of the educational policy-making process that can produce information that is used to improve the education policy. The measurement of the success of educational policies is one of the most important tools in an educational policy evaluation activity that is used as a measurement of the value and benefits resulting from the implemented educational policies.